Legal Aspect of Binary Options Broker Platform Related to Operating Permissions From Bappebti and Liability of Company’s Information From Blocked Social Media - Andersen, Christian; Haykal, Hassanain; Kurniawan, Shelly; Rachelia, Callista (Technium Social Sciences Journal, 2023)
It seems that we are bombarded every day with advertisements touting the benefits of investing online through binary options brokers (Binary Options). Pop ups on various social media showing celebrities and their yachts, and driving luxury cars and luxury vacations on their own Tropical Islands. However, due to a lack of information, many have stuck with this risky fantasy, and this has been proven again, investing is not a game, and many people who think they can make a fortune trading online quickly eat up years of savings. This research applied a normative legal study using statutes, conceptual, and case approaches. The legal materials were through document study, i.e., reviewing regulations and concepts relevant to investment law. Data in this research were analyzed qualitatively. The result research shows that many people make promises to the public that online trading can generate large profits as additional income. In practice, it is said through it money will work for us. Even though the risk of loss that can occur is also very large or commonly known as a highrisk high return. Public enthusiasm for transactions in the field of Commodity Futures Trading during the pandemic has increased. For this reason, supervision and observation needs to be tightened to prevent potential losses to the public due to unlicensed offers of advertisements and promotions in the field of Commodity Futures Trading and one of the ways is by imposing restrictions so that the websites of these unlicensed entities cannot be accessed. Entity applications that do not have permission from Bappebti, which are still on the Google Playstore and IOS Appstore, and socialized by various influencers-celebs on social media contain elements of fraud and their legality is questionable.